The influence of psychological capital, job satisfaction and human capital management - Made Angga Palguna; Andreas Wahyu Gunawan (Junal Ilmu Manajemen, 2023)
This study aims to analyze the influence of psychological capital, job satisfaction and human capital management on employee performance with employee engagement as a mediating variable at PT. HI. This study uses a quantitative method that uses primary data sourced from questionnaires distributed via google form to employees at PT HI. The research sample was selected using purposive sampling method with a population of 254 employees, so that 155 employees were obtained as samples. Data analysis used for hypothesis testing is Covariance-Based Structural Equation Modeling (CB-SEM) and the software used is AMOS and to test the hypothesis of mediating variables using the Sobel Test. The results of this study indicate that there are several hypotheses that have a positive effect including; psychological capital on employee engagement, job satisfaction on employee engagement, employee engagement on employee performance, psychological capital on employee performance, job satisfaction on employee performance, and job satisfaction on employee performance through employee engagement. In addition, the results also found information that there is no positive influence between human capital management on employee engagement, human capital management on employee performance, psychological capital on employee performance through employee engagement, and human capital management on employee performance through employee engagement.